Correlation of the Plasma Concentration of Eltrombopag With Efficacy in the Treatment of Refractory Aplastic Anemia: A Single-Centre Study in China - Wei Zuo; Bo Zhang; Jing Ruan; Miao Chen; Bing Han (Frontiers Media S.A., 2020)
Background and purpose: Eltrombopag (ELT) can be effective in the treatment of relapse/refractory aplastic anemia (AA) patients. Responses and adverse drug reactions (ADRs) differed greatly among individuals treated at the same dosage of ELT.Methods: Patients diagnosed with nonsevere aplastic anemia (NSAA) between January 2018 and January 2019 in Peking Union Medical Colleague Hospital who were refractory to immunosuppressive therapy were treated with ELT and followed up for at least 6 months. Plasma concentrations of ELT were detected by high-performance liquid chromatography-mass spectrometry after at least two months of ELT treatment and treatment at the same dosage for at least 2 weeks. The dose-concentration, concentration-response and concentration-ADR relationships were evaluated.Results: Among the 72 patients treated with ELT during the study period, 44 patients with complete data were enrolled. Six (13.6%) were males, and 38 were females (86.4%), with a median age of 54 years [interquartile range (IQR): 38.5-63]. At the time the ELT plasma concentration was detected, the median dosage of ELT was 75 (IQR 50-100) mg/d, the median time of total ELT exposure was 3 (IQR 2.0-6.0) months, and 37 (70.5%) patients had responded to ELT. The median concentration of ELT was 10.4 μg/ml (IQR 3.7-24.4 μg/ml). The concentration of ELT was positively correlated with the daily dose of ELT (r = 0.68, p < 0.001). Multivariate logistic regression analysis showed that the risk of inefficacy of ELT at a concentration between 11.2 and 15.2 μg/ml was 0.028-fold (95% CI: 0.001-0.864; p = 0.041) of that at a concentration between 3.2 and 7.2 μg/ml. The cutoff value for the concentration of ELT showing efficacy was 12.50 μg/ml according to the receiver operation characteristic curve. A higher risk of ADR was related to a longer total exposure to ELT (p = 0.012). Although the correlation was not significant, the odds ratio increased with the ELT concentration, suggesting that it was possible that an elevated risk of ADR was correlated with the ELT blood concentration.Conclusion: ELT is effective for the treatment of NSAA and has acceptable side effects. The plasma concentration of ELT was correlated with the dose and the effects of ELT.